Decisiones de producción, capacidades de producción y prioridades competitivas: Un estudio aplicado al sector de metal en Espa\~na - B. Urgal González; J. M. García Vázquez (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
The objective of this study is to examine the relationship between the implementation of decisions and policies that originate manufacturing capabilities (flexible plant automation, design and manufacturing engineering, quality management and control systems, empowerment) and the importance the company attaches to certain competitive priorities in its business strategy. Information for the data base was obtained by means of a postal survey to companies in the metal sector, with over 50 employees, established in Spain in 2001, the year of reference for the study. The results suggested that implementing certain production decisions and policies can enable a company to acquire capabilities that can act as a basis for a competitive advantage.
Keywords: 330; flexible plant automation; design and manufacturing engineering; quality management and control systems; empowerment; manufacturing capabilities; competitive priorities